Risk Communication For Community Preparedness In Flood Disaster - Prasojo Prasojo (Cita Konsultindo Research Center, 2023)
Indonesia is the third country with flooding potential after India and China, especially in its low-land areas. Flood disasters certainly risk the surrounding community. Therefore these risks need to be understood, managed and communicated beforehand so that people can lead a better life. Thus, risk communication is needed. With the implementations of risk communication so far in society, this research applies the literature review method. This method includes several steps, including identifying, assessing, and providing interpretation of the literature. As a result, many people still prefer to develop risk communication independently and deal with disasters based on personal experience due to the low level of public trust in the government. Future research then requires an approach to formulate effective flood risk communication steps and techniques for use by disaster-prone communities.